2021
DOI: 10.3389/fpsyg.2021.640474
|View full text |Cite
|
Sign up to set email alerts
|

Kindergarten Obesity and Academic Achievement: The Mediating Role of Weight Bias

Abstract: This study draws the attention towards the importance of reducing weight discrimination against children for their educational success, as an issue of social justice. We investigate the consequences of early-onset obesity identifying the mediating mechanisms in the relationship between childhood obesity and academic achievement. To do so, we employ the Early Childhood Longitudinal Study-Kindergarten Cohort (kindergarten to fifth grade) in the US (ECLS-K: 2011) and apply a parallel process latent growth model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 86 publications
(129 reference statements)
0
13
1
1
Order By: Relevance
“…Four studies (from the US and Canada) reported no association 15–18 . The final study of the eight showed sex differences, 8 which have also been demonstrated in a further study published since the systematic review 19 . Developing overweight between kindergarten and primary school was associated with lower scores in math and reading tests for US girls, but not boys 8 .…”
Section: Introductionmentioning
confidence: 63%
See 4 more Smart Citations
“…Four studies (from the US and Canada) reported no association 15–18 . The final study of the eight showed sex differences, 8 which have also been demonstrated in a further study published since the systematic review 19 . Developing overweight between kindergarten and primary school was associated with lower scores in math and reading tests for US girls, but not boys 8 .…”
Section: Introductionmentioning
confidence: 63%
“…We also found that weight status was more strongly associated with future academic achievement for girls, compared with boys. Similarly, Yu and colleagues indicated those who were affected by overweight and obesity in kindergarten had poorer reading and math achievement in primary school among US children, particularly for girls 19 . Datar and Sturm 8 also found that girls (but not boys) who became affected by overweight between kindergarten entry and end of Year 3 had lower Year 3 math and reading scores, compared with those who remained healthy weight.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations